Musical collections and family traditions - Korzh, L.M. (Perm Federal Research Centre Journal, 2018)
The long-term project «Gribushin’s Assemblies in the Perm Scientific Center of the UB RAS» (now PFRC UB RAS) was launched in autumn 2015. It replaced the concert evenings of the Classical Music Fan Club of the PSC UB RAS. The twenty-year-old history of those evenings is associated with revival of the traditionsofchambermusicperformances.Thecharacteristicfeatureofthe Club’sevenings(morethan 200) was the unification into thematic cycles where the creative pursuits of talented Perm musicians were ideally combinedwiththehistoryofGribushin’mansionandtheworkofoneofprominentarchitectsA.B.Turchevich. Over the past years the old Gribushin’s House, one of A.B. Turchevich’s masterpieces, has become a traditional place for meetings of representatives of academic science, especially for those whose leisure-time is associated with classical music. In the new format of the Gribushin’s Assemblies it is the personality of a scientist that is in the focus. The assemblies combine two main events: a popular science report and a concert programme, the latter being emotionally and contextually related to the scientific part of the evening.